Victimisation of Married Pakistani Women from Three Types of Aggression Perpetrated by their Mother-in-Law, and Mental Health Concomitants - Khan, Taalia; Österman, Karin; Björkqvist, Kaj (Technium BioChemMed, 2021)
The aim of the study was to investigate victimisation of married women from aggression perpetrated by the mothers-in-law, and its psychological concomitants. A questionnaire was completed by 569 married women in Pakistan. The mean age was 31.4 years (SD 9.1). Mothers-in-law perpetrated more verbal and indirect aggression than physical aggression against their daughters-in-law. Anxiety, depression, obsessive compulsive symptoms, and somatisation were all associated with aggression perpetrated by the mothers-in-law. The mothers-in-law had significantly more often than the husbands perpetrated indirect aggression against the daughters-in-law, while the husbands had perpetrated both physical and verbal aggression against their wife significantly more often than the mothers-in-laws. It was concluded that aggression perpetrated by mothers-in-law is a significant problem and associated with mental health problems in married Pakistani women.